LIGHT ABSORPTION CAPACITY OF FLOWERS OF THE INVASIVE SPECIES AMBROSIA ARTEMISIIFOLIA L. - Fedenko, Володимир (Biota. Human. Technology, 2025)
The purpose of the work. Determining the light absorption capacity of common ragweed flowers. Methodology. The selection of male flowers was carried out at the flowering stage in the upper part of the plant crown, where the plants receive the maximum amount of light and this process occurs most intensively. Reflectance spectra were obtained in the range of 350–800 nm. Colorimetric parameters were determined in the CIE XYZ and CIE L*a*b* systems. For additional identification of flavonoids, flowers were extracted with isopropanol and chemisorption of compounds from the extract on the surface of aluminum oxide was performed with subsequent determination of spectral characteristics. Scientific novelty. Reflectance and colorimetric characteristics determined for the first time to confirm the photoprotective effect of UV-absorbing flavonoids in common ragweed flowers. Conclusions. A defining feature of the reflectance spectra of flowers of the invasive species Ambrosia artemisiifolia as a heliophyte is an increase in the intensity of the maximum of UV-absorbing flavonoids compared to carotenoids and chlorophylls. To increase the degree of distribution of the detected maxima, the spectral reflectance curve was differentiated. The reflectance characteristics of the flowers resulted in a stimulus with a dominant wavelength in the yellow range. The increased localization of flavonoids in the surface tissues of flowers causes an increase in the photoprotective ability as an adaptive enhancement of the reproductive system of the invasive species. Flavonoids were identified due to their chelating properties by chemisorption from plant extract on aluminum oxide. As a result of the sorption interaction, a yellow-green adsorbate was obtained. The presence of flavonoids in the adsorbate was confirmed by spectral characteristics. The obtained results confirm the role of phenolic compounds in increasing the competitiveness of invasive plants according to the shifting defence hypothesis. The proposed methodological approaches can be applied to identify invasive species at the flowering stage and when using the resource potential of these plants to obtain biologically active substances.